2002
DOI: 10.1124/mol.62.4.847
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Cell Surface Insulin Receptor and Insulin Receptor Substrate-1 Phosphorylation by Inhibitor of 90-kDa Heat-Shock Protein Family: Endoplasmic Reticulum Retention of Monomeric Insulin Receptor Precursor with Calnexin in Adrenal Chromaffin Cells

Abstract: Treatment (Ն6 h) of cultured bovine adrenal chromaffin cells with geldanamycin (GA) or herbimycin A (HA), an inhibitor of the 90-kDa heat-shock protein (Hsp90) family, decreased cell surface 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 40 publications
(88 reference statements)
1
33
0
Order By: Relevance
“…If this reflects the situation in vivo, this would explain the preserved insulin action mediated by impaired insulin clearance in spite of a small reduction in the total number of insulin receptors. In cell lines transfected with other kinase-deficient INSR mutations, accelerated receptor degradation has been reported to involve heat shock protein 90 (HSP90) [33], and recently the inhibition of HSP90 was shown to reduce the levels of functional non-mutated insulin receptors on the cell surface [34]. These studies suggest that HSP90 may serve to increase the amount of non-mutated relative to mutated insulin receptors.…”
Section: Discussionmentioning
confidence: 97%
“…If this reflects the situation in vivo, this would explain the preserved insulin action mediated by impaired insulin clearance in spite of a small reduction in the total number of insulin receptors. In cell lines transfected with other kinase-deficient INSR mutations, accelerated receptor degradation has been reported to involve heat shock protein 90 (HSP90) [33], and recently the inhibition of HSP90 was shown to reduce the levels of functional non-mutated insulin receptors on the cell surface [34]. These studies suggest that HSP90 may serve to increase the amount of non-mutated relative to mutated insulin receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Total quantities of cellular proteins, as measured by the Noninterfering Protein Assay kit, were not changed between nontreated and ketone body-treated or acidic medium-treated cells. The same amounts of proteins (7.0 -7.5 g/lane) were separated by SDS-7.5% polyacrylamide gel electrophoresis (PAGE) and transferred onto a nitrocellulose membrane; it was preincubated with 5% dry milk in phosphate-buffered saline and reacted overnight at 4°C with rabbit antibody against the C-terminal amino acid sequence (1365-1382) of the IR ␤-subunit (Cheatham and Kahn, 1995;Shiraishi et al, 2000Shiraishi et al, , 2001Yamamoto et al, 2000;Saitoh et al, 2002). After repeated washings, the immunoreactive bands were labeled with 125 I-anti-rabbit IgG (1:1000) and analyzed by a Bioimage BAS 2000 analyzer (Fuji Film, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study showed that chaperone function of the heat shock protein 90-kDa family was indispensable to the homodimerization of monomeric IR precursor at the ER (Saitoh et al, 2002). Protein kinase C-␣ increased IR mRNA and protein levels, thus causing up-regulation of cell surface IR (Yamamoto et al, 2000).…”
mentioning
confidence: 99%
“…Some of the receptors are directed back to the plasma membrane in clatrin-coated vesicles, while others are degraded in lysosomes [3,122].…”
Section: Human Insulin Receptor's Structurementioning
confidence: 99%
“…The INSR precursor is subsequently proteolytically cleaved in trans Golgi to form the mature INSR protein which is then transported to the cell's surface [122]. The growing polypeptide chain of the insulin receptor translocates through the Sec61 translocon to the endoplasmic reticulum lumen [5].…”
Section: Human Insulin Receptor's Structurementioning
confidence: 99%